(3cJGH aj hUa GdCQV hGdSfjf hGdTghQ hGdfHGJs
(3ChdgG (B:s
(3hMLQgG GdajQhRL , hJQGHgG Wjf GdEKeO GdPi dGjhLO eKdg ai GdCQV , hjMed Ydi RQhf fjSGHhQ Edi COfi GdCQV hCbGUjgG hjJMa Hg Gdedhc hGdSGOI s
(3BNQgG (B:s
(3hdeG NQL jhfS Ydjg GdSdGe ef HWf GdMhJ NQL cGdWad Mjf jNQL ef HWf Ceg , aCfHJ Gddg SHMGfg hJYGdi ai GdMGd TLQI ef jbWjf MJi JUdHJ HTQJg hLGA ai GdMOjK Cf GdfHi Udi Gddg Ydjg hSde cGf jJJHY GdOHG s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3Hg eWGdH ddcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs